Association of variations in HLA class II and other loci with susceptibility to EGFR-mutated lung adenocarcinoma - Kouya Shiraishi (Nature Portfolio, 2016)
EGFR mutations in lung adenocarcinoma are more frequent in East Asians compared to other populations. Here, the authors carry out a genome-wide association study in EGFRmutant cancers and identify loci that are associated with risk of developing this molecular subtype of cancer.